2020
DOI: 10.1007/s10533-020-00673-8
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric deposition of elements and its relevance for nutrient budgets of tropical forests

Abstract: Atmospheric deposition is an important component of the nutrient cycles of terrestrial ecosystems, but field measurements are especially scarce in tropical regions. In this study we analysed 15 months of precipitation chemistry collected in an old growth tropical forest located in French Guiana. We measured nutrient inputs via bulk precipitation and throughfall and used the canopy budget model to estimate nutrient fluxes via canopy exchange and dry deposition. Based on this method we quantified net fluxes of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 99 publications
2
33
2
Order By: Relevance
“…Large buildup of organic matter (up to 2 m close to tree trunks) with resident times of up to 78 years (Silvester & Orchard, 1999) partly explains the lower nutrient return through litterfall. Similar findings have been reported from exotic conifer stands in New Zealand where throughfall reaching the soil under Douglas fir contained twice as much K as litterfall (Will, 1959), while atmospheric deposition plus canopy leaching delivered three times more K to the soil than the internal nutrient recycling via litterfall (van Langenhove et al, 2020). Nutrient input by throughfall and forest floor leachates may be critical in sustaining forest productivity, particularly in ecosystems characterized by low soil nutrient availability, such as kauri forests (Steward & Beveridge, 2010;Verkaik et al, 2006).…”
Section: Internal Transfer Of Nutrientssupporting
confidence: 85%
See 1 more Smart Citation
“…Large buildup of organic matter (up to 2 m close to tree trunks) with resident times of up to 78 years (Silvester & Orchard, 1999) partly explains the lower nutrient return through litterfall. Similar findings have been reported from exotic conifer stands in New Zealand where throughfall reaching the soil under Douglas fir contained twice as much K as litterfall (Will, 1959), while atmospheric deposition plus canopy leaching delivered three times more K to the soil than the internal nutrient recycling via litterfall (van Langenhove et al, 2020). Nutrient input by throughfall and forest floor leachates may be critical in sustaining forest productivity, particularly in ecosystems characterized by low soil nutrient availability, such as kauri forests (Steward & Beveridge, 2010;Verkaik et al, 2006).…”
Section: Internal Transfer Of Nutrientssupporting
confidence: 85%
“…Solution collected underneath the forest floor (forest floor leachate) is often greatly enriched in nutrients compared to bulk precipitation and canopy water fluxes due to the leaching of nutrients from organic matter (Batjes, 1996). Nutrient transfer to the soil by throughfall deposition and forest floor leachates is an important input pathway, particularly in ecosystems where nutrient return through litterfall decomposition is slow (van Langenhove et al, 2020;Will, 1959) and in ecosystems with low soil nutrient availability (Forti & Moreira-Nordermann, 1991;Moslehi et al, 2019;Parker, 1983).…”
mentioning
confidence: 99%
“…Despite the spatial heterogeneity of its sources, desert dust is often highly enriched in P, with concentrations far higher than those in most soils (Bristow et al ., 2010; Gross et al ., 2015a). In ecosystems with poor soil P and high rates of dust deposition, yearly dust P inputs can be of the same magnitude as litterfall P inputs (Okin et al ., 2004; Gross et al ., 2015b; Van Langenhove et al ., 2020). Hence, dust deposition may support a large fraction of the ecosystems’ net primary productivity and P demand (Cleveland et al ., 2013; Runyan et al ., 2013; Wang et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research in French Guiana, especially in Paracou, indicated that soil P stocks and soil extractable P are low (Allié et al., 2015; Sabatier et al., 1997; Soong et al., 2020). Additionally, a recent study of BNF and its drivers in French Guiana identified P as a regulating driver for soil BNF in Paracou, with higher soil P responsible for higher BNF rates (Van Langenhove et al., 2019). That same study, however, did not identify Mo as regulating driver for soil BNF, even though it clearly caused an increase in Nouragues soil BNF rates here (Figure 3a).…”
Section: Discussionmentioning
confidence: 99%
“…It is highly likely that the addition of P to the litter layer at least partially relieved the P constraints present in the litter, just as suspected by Vitousek and Hobbie (2000) and Reed et al (2013) in their respective studies. The global increase in P deposition (R. Wang et al, 2017), already measurable in French Guiana (Barkley et al, 2019;Van Langenhove et al, 2020), is thus likely to cause increases in litter BNF at our forest sites. As for Mo, the P fertilizer we added in the field contained Mo as a hidden trace element (<0.15 mg/kg), shedding doubt on the validity of our results following P additions (Barron et al, 2009).…”
Section: The Effects Of P and Momentioning
confidence: 92%